1968
DOI: 10.1037/h0025910
|View full text |Cite
|
Sign up to set email alerts
|

Skill versus chance activity preference and locus of control.

Abstract: lfillm e n t of th e r e q u ir e m e n ts f o r th e ,5^--------------------------------------'% / * L '-j DISSERTATION C O M M IT T E E A CKNOWLE DGEMENTT h e w r i te r w is h e s to th a n k th e e x p e rim e n ta l s u b je c ts , ju d g e s andh is c o m m itte e m e m b e r s fo r th e tim e an d e ffo rt th e y ex p en d ed . H e a lso w is h e s to th a n k S a lly S c h n e id e r fo r h e r e d ito r ia l a s s is ta n c e an d e n c o u r a g e m e n t th ro u g h o u t; M r s . G ay B a r tle y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…rela ted to overt death anxiety (212) . Other studies (123,192) provided results which were general ly consistent with theory.…”
Section: Conceptual-operational Coordination and Validation Of Measuressupporting
confidence: 80%
“…rela ted to overt death anxiety (212) . Other studies (123,192) provided results which were general ly consistent with theory.…”
Section: Conceptual-operational Coordination and Validation Of Measuressupporting
confidence: 80%
“…It has been suggested (Gold, 1966;Schneider, 1968) that internally oriented subjects would prefer skilled tasks which would confirm their control over reinforcements, whereas externally oriented subjects would prefer chance activities because they do not believe in their ability or performance. Gold (1966) found no relationship between I-E scores and choice of a skill or a chance task.…”
Section: The Correlational Studymentioning
confidence: 96%
“…Whereas internals, compared with externals, have consistently been found to prefer and perform better on skill-determined tasks, externals have been shown to express a greater preference for chance tasks than do internals and even to prefer chance tasks to skill tasks (e.g., DuCette & Wolk, 1973;Kahle, 1980;Schneider, 1968Schneider, , 1972. Rotter and Mulry (1965) found that externals consult fortune-tellers and have their horoscopes read more often than do internals, and DuCette and Wolk (1973) found that externals showed a greater preference for an extrasensory perception task than did internals.…”
Section: Locus Of Control and Behavior In Chance Situationsmentioning
confidence: 99%